Polymer composite materials: A comprehensive review - Hsissou, Rachid; Seghiri, Rajaa; Benzekri, Zakaria; Hilali, Miloudi; Rafik, Mohamed; Elharfi, Ahmed (Composite structures, 2021)
•Polymer composite materials were reinforced by organic and/or inorganic fibers and formulated by various fillers.•Composite materials have an excellent mechanical and thermal properties.•Composite materials have a best abrasion resistance and exceptional electric insulation. Herein, in the present review we developed and investigated a comprehensive review of advanced composite materials based on thermoplastic polymers, elastomer polymers and thermosetting polymers. These advanced composite materials were reinforced by organic and/or inorganic fibers and formulated using various fillers such as organic, mineral and metallic. Further, we present the development and the synthesis of several macromolecular matrices namely polycarbonate, polyhexamethylene sebacic, polyether sulfone, polyether ether ketone, polyether ketone ketone, polyether imide, polyethylene terephthalate, phenoplasts, epoxy resin and polyurethane. The advantage of composite materials formulating is to have excellent mechanical performances, high thermal resistance, good fire behavior, high impact resistance, best abrasion resistance, exceptional electric insulation and good rigidity. Then, composite materials formulation were examined and discussed in detail.